Maize/peanut intercropping has greater synergistic effects and home-field advantages than maize/soybean on straw decomposition - Surigaoge, Surigaoge; Yang, Hao; Su, Ye; Du, Yu-He; Ren, Su-Xian; Fornara, Dario; Christie, Peter; Zhang, Wei-Ping; Li, Long (Frontiers in Plant Science, 2023)
The decomposition of plant litter mass is responsible for substantial carbon fluxes and remains a key process regulating nutrient cycling in natural and human-managed ecosystems. Litter decomposition has been addressed in agricultural monoculture systems, but not in intercropping systems, which produce species-diverse litter mass mixtures. Three decomposition experiments were conducted over 341 days in a long-term intercropping field experiment, which included 2 nitrogen (N) addition levels (no-N and N-addition) and 5 cropping systems (monoculture maize, soybean and peanut, maize/soybean and maize/peanut intercropping). Experiment I was used to quantify litter quality effects on decomposition: five types (maize, soybean, peanut, maize-soybean and maize-peanut mixture) of straw from two nitrogen treatments decomposing in the same maize plot; Experiment II addressed soil environment effects on root decomposition: soybean straw decomposed in different plots (5 cropping systems and 2 N levels). Experiment III addressed ‘home’ decomposition effects whereby litter mass (straw) was left to decompose in the plot of origin. The contribution of litter and soil effects to the home-field advantages was compared between experiment III (‘home’ plot) and I-II (‘away’ plot). Our results show how straw types affected litter mass loss in the same soil (experiment I) and in the ‘home’ plot environment (experiment III). Cropping systems did not affect the mass loss of soybean straws (experiment II). N-addition significantly increased straw mass loss in experiment III. Peanut straw and maize-peanut straw decomposition clearly benefited from ‘home-field advantage’ effects more than maize and soybean straws. There was a synergistic mixing effect of maize-peanut and maize-soybean straw mixture decomposition in both home (experiment III) and ‘away’ plots (experiment I). Maize-peanut showed greater synergistic effects and ‘home-field advantages’ than maize-soybean in straw mixture decomposition in their home plot (experiment III). We discuss how these findings can have important implications for the management of species-diverse straw in intercropping systems.